2020
DOI: 10.21203/rs.3.rs-34049/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrated analysis of RNA binding proteins in human colorectal cancer

Abstract: Background: Though RNA-binding proteins play an essential role in a variety of different tumors, there is still limited effort made on the systematic analysis of RNA binding proteins (RBPs) in the survival of colorectal cancer(CRC).Methods: An analysis was conducted of the CRC transcriptome data collected from the TCGA database and RBPs were extracted from CRC. R software was applied to analyze the differentially expressed genes (DEGs) of RBPs. To identify the pathways and functional annotation of RBPs DEGs, G… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…For example, Liu et al suggested that fetal-lethal noncoding developmental regulatory RNA (FENDRR) as an anti brotic long noncoding RNA can reduced pulmonary brosis by inhibiting broblast activation by reducing iron concentration, which may act as a potential therapeutic target for pulmonary brosis [16] . Aberrant expression of lncRNAs related with iron metabolism has been participated in regulating critical physiological functions which were linked to different types of cancer in present studies [17][18][19]. Moreover, a review revealed that hepatic iron accumulation can lead to brotic responses, and the signi cance and potential of iron-related proteins in the progression and development of liver brosis [20] .…”
Section: Introductionmentioning
confidence: 81%
“…For example, Liu et al suggested that fetal-lethal noncoding developmental regulatory RNA (FENDRR) as an anti brotic long noncoding RNA can reduced pulmonary brosis by inhibiting broblast activation by reducing iron concentration, which may act as a potential therapeutic target for pulmonary brosis [16] . Aberrant expression of lncRNAs related with iron metabolism has been participated in regulating critical physiological functions which were linked to different types of cancer in present studies [17][18][19]. Moreover, a review revealed that hepatic iron accumulation can lead to brotic responses, and the signi cance and potential of iron-related proteins in the progression and development of liver brosis [20] .…”
Section: Introductionmentioning
confidence: 81%
“…Given that RBPs are critical regulators and effectors of cancer, they also should be regarded as hallmarks and potential targets for early diagnosis, prognosis and clinical intervention of cancer. NOP14/MRPS23/POP1 exhibit prognostic value in colorectal cancer, while APOBEC3C/DCAF13/EIF4E3/EZR possess significance in predicting prognosis of breast cancer ( 17 , 18 ). Moreover, the Ribavirin, an antiviral guanosine analog, is able to slacken tumorigenesis by competitively interacting with the 5’-Cap of eIF4E mRNA, subsequently impeding the translation and transposition of eIF4E-regualted Cyclin D1 ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies showed that the abnormality of RBPs was related to lung cancer [11], glioma [12], colorectal cancer [13]and hepatocarcinoma [14]. It was reported that human ribosomal protein S3 (RPS3) served as a variety of novel pro-tumorigenic RBP in hepatocarcinoma, and RPS3 could bind to the 3' UTR of SIRT1 mRNA in hepatocarcinoma, resulting in the stable expression of the oncogene SIRT1 [14].…”
Section: Introductionmentioning
confidence: 99%